Succession and Partition of Shares - Dimitrov, Miroslav (Research Papers, 2021)
The article addresses the issue of inheritance of shares and the problems that arise with more than one heir. The practice of the Supreme Court of Cassation in the last few years is followed, according to which the shares are not inherited as receivables and their automatic distribution among the heirs according to the inheritance quotas does not occur, but co-ownership of each of the inherited shares arises. This thesis is also supported in legal theory. On the other hand, according to settled case law, shares are not subject to judicial partition. The latter raises an unsolvable problem for establishing individual possession of the inherited shares by the heirs and exercising the rights under them in cases when the heirs have insurmountable contradiction so that agreement on their distribution and even appointment of a common proxy under Art. 177 of the Commercial Code are not possible. Solutions to the problems by amending or supplementing the current law or by changing its interpretation are proposed.EL: К15, К40
Keywords: Shares; Shareholder; Heir; Indivisibility; Partition; Succession